Core–shell particles for controllable release of drug. (24th March 2015) - He, Dinggeng; Wang, Shuo; Lei, Lei; Hou, Zengtao; Shang, Peng; He, Xiaoxiao; Nie, Hemin
Abstract: In this review paper, the state-of-the-art knowledge on core–shell particles for controllable release of drug(s) is presented. Two categories of core–shell particles, including core–shell mesoporous silica nanoparticles and core–shell polymeric particles, have been investigated. The fabrication methods and specific drug release mechanisms for different core–shell particles are thoroughly reviewed with detailed examples. Highlights: The state-of-the-art knowledge on core–shell particles for controllable release of drug is presented. Core–shell mesoporous silica nanoparticles are suitable for activatable release of drug. Core–shell polymeric particles can be employed to produce parallel and sequential release patterns of drugs.